2000
DOI: 10.1093/brain/123.7.1471
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of MRI lesions with visual psychophysical deficit in secondary progressive multiple sclerosis

Abstract: The aim of this work was, first, to clarify the nature of the relationship between the sensory deficit in the demyelinated visual pathway and morphological changes revealed by MRI and, secondly, to test whether there was a preferential effect of demyelination for either the magnocellular or parvocellular pathway in established multiple sclerosis. Twenty-four patients with secondary progressive multiple sclerosis were studied psychophysically and by MRI of the optic nerve and brain. MRI was performed with a Phi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…The color CFF procedure detected more pronounced color vision impairment in patients with optic neuritis than in patients with diabetic retinopathy. These findings agree with previous studies that used objective or subjective tests and reported altered chromatic sense in these patients [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. As expected, we found a preferential impairment for red stimuli in patients with optic neuritis and for blue stimuli in patients with diabetic retinopathy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The color CFF procedure detected more pronounced color vision impairment in patients with optic neuritis than in patients with diabetic retinopathy. These findings agree with previous studies that used objective or subjective tests and reported altered chromatic sense in these patients [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. As expected, we found a preferential impairment for red stimuli in patients with optic neuritis and for blue stimuli in patients with diabetic retinopathy.…”
Section: Discussionsupporting
confidence: 93%
“…Among current techniques for assessing visual system integrity in patients with optic neuritis or degenerative retinopathy [16][17][18][19][20][21][22][23][24][25][26][27][28][29]36] electrophysiological (i.e. color evoked potentials) and psychophysical (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral constriction in visual fields is a common find in MS patients, frequently related to a cortical atrophy or retrochiasmal damage in visual pathway [116,[119][120][121][122]. Additionally, spatial and temporal resolutions are also affected since the demyelination insult impairs the brainstem and also subcortical areas [123][124][125][126][127] evidenced by imaging studies [128].…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Earlier studies addressing visual function in ON have emphasized colour vision deficits [2][3][4][5] and suggested that the parvocellular stream, as compared to the magnocellular stream, is preferentially impaired in ON. However, these studies [2][3][4] focused on foveal vision, equated the magnocellular pathway with a pure luminance stream, and used a relatively low number of patients, with heterogeneous clinical status (some chronic, some subacute).…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies [2][3][4] focused on foveal vision, equated the magnocellular pathway with a pure luminance stream, and used a relatively low number of patients, with heterogeneous clinical status (some chronic, some subacute). In an additional study [5], the relative isolation of parvocellular versus magnocellular (luminance) pathways was not optimized, given that temporal and spatial frequencies were neither explicitly manipulated nor optimized for functional separation.…”
Section: Introductionmentioning
confidence: 99%